1999
DOI: 10.1016/s0002-9440(10)65111-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency Accelerates Autoimmune Exocrinopathy in Murine Sjögren's Syndrome through Fas-Mediated Apoptosis

Abstract: Estrogenic action has been suggested to be responsible for the strong female preponderance of autoimmune diseases, but the role of estrogens in the female has not been well characterized. We evaluated the effects of estrogen deficiency in a murine model for autoimmune exocrinopathy of Sjögren's syndrome (SS). Severe destructive autoimmune lesions developed in the salivary and lacrimal glands in estrogen-deficient mice, and these lesions were recovered by estrogen administration. We detected an intense estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
1
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 55 publications
(34 reference statements)
6
81
1
8
Order By: Relevance
“…Recent evidence suggests that apoptosis plays a key role in the physiology and pathogenesis of various autoimmune diseases (2,7,19,35,42). We have demonstrated that estrogenic action influences target epithelial cells through Fas-mediated apoptosis in a murine model for Sjögren's syndrome (13). Recently, we found that tissue-specific apoptosis in the exocrine glands spontaneously occurring in estrogen-deficient mice may contribute to the development of autoimmune exocrinopathy (14).…”
mentioning
confidence: 97%
“…Recent evidence suggests that apoptosis plays a key role in the physiology and pathogenesis of various autoimmune diseases (2,7,19,35,42). We have demonstrated that estrogenic action influences target epithelial cells through Fas-mediated apoptosis in a murine model for Sjögren's syndrome (13). Recently, we found that tissue-specific apoptosis in the exocrine glands spontaneously occurring in estrogen-deficient mice may contribute to the development of autoimmune exocrinopathy (14).…”
mentioning
confidence: 97%
“…In late-phase diabetes, an increase in the number of autophagic structures occurs in granular duct cells. The histological findings from non-obese diabetic mice's submandibular gland tissues also indicate damage accompanied by massive cell infiltration [28][29][30][31]. Some studies have shown that oestrogen and progesterone regulate the structure and function of the submandibular glands.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Previously, we demonstrated that estrogenic action influences target epithelial cells through Fas-mediated apoptosis in a murine model of SS. 27 Moreover, we found that the tissue-specific apoptosis in the exocrine glands spontaneously occurring in estrogen-deficient healthy C56BL/6 (B6) mice may contribute to the development of autoimmune exocrinopathy resembling SS. 28 Recently in minor salivary glands from patients with SS, significantly increased development of IFN pathways and increased plasmacytoid dendritic cells (pDCs) as a possible source of IFN were shown.…”
mentioning
confidence: 83%
“…27,28 Briefly, mouse submandibular glands were minced into 1-mm 2 pieces, digested with collagenase (750 U/ml of type I) and hyarulonidase (500 U/ml of type IV) in Dulbecco's modified Eagle's medium containing 10% fetal calf serum. The digested suspension was passed through a 75-m nylon mesh filter.…”
Section: Preparation and Primary Culture Of Mouse Salivary Glands Susmentioning
confidence: 99%